Processes of disembedding and displacement: anomie and the juridification of religio-ethnic identity in post-New Order Bali - Ramstedt, Martin (Asian Ethnicity, 2012)
This article applies Karl Polanyi's observation of a double movement of law in the history of nineteenth and early twentieth-century Europe to an analysis of Bali's integration into the global cultural economy. It describes how the increasing disembedding of the island's tourist industry from local norms and institutions, and the parallel disjuncture between Balinese religiosity and Indonesian state religion have created a condition of increasing collective anomie that has in turn provoked endeavors to juridify the Balinese religio-ethnic identity. Conceding the partial success of the juridification process that has been facilitated by the recent governance reform, and that has indeed effected a significant degree of re-embedding both tourism and religion into local culture, the article argues that not only has the anomic condition not been attenuated; the potential for internal conflict and division has even been enhanced.
Law; Anthropology
Keywords: Bali; Balinese (Indonesian people); Europe; POLANYI; Karl; 1886-1964; anomie; decentralization; decentralization in government; disembedding; ethnicity; identity; juridification; religiousness

The roots of the global economic crisis (Respond to this article at http://www.therai.org.uk/at/debate) - Hart, Keith (Anthropology Today, 2012)
The world economic crisis should be seen as an episode in the history of money. “National capitalism” was the main way of organizing money in the twentieth century and its symbol was national monopoly currency. This system has been unravelling since the US dollar de-pegged from gold in 1971. The result is a disconnect between politics which are still largely national and the money circuit which is decentralized and global. The work of Georg Simmel and Karl Polanyi is enrolled to explain this development which entails the loss of money's physical substance, a shift in the social institutions supporting it and a break-up of the forms and functions of “all-purpose money”. The euro crisis reveals the historical mistake of treating market economy as a driver of society and politics. Good intentions at this stage will not reverse what has become a Greek tragedy in more senses than one.
Anthropology
Keywords: global economic crisis

A Handbook of Economic Anthropology, Second Edition - Carrier, James G. (Edward Elgar Publishing, 2012)
Acclaim for the first edition: 'The volume is a remarkable contribution to economic anthropology and will no doubt be a fundamental tool for students, scholars, and experts in the sub-discipline.' _ Mao Mollona, Journal of the Royal Anthropologica
Anthropology
Keywords: business & economics; cultural anthropology; cultural policy; economic anthropology; macroeconomics; political science; popular culture; public policy; social science

A Handbook of Economic Anthropology, Second Edition: Orientations: Karl Polanyi - Isaac, Barry L. (A Handbook of Economic Anthropology, Second Edition, 2012)
Anthropology
Keywords: capitalist systems; economic anthropology; economic history; economic sociology; history of economic thought: individuals; political economy; social and economic stratification

Karl Polanyi E O ‘Grande Debate’ Entre Substantivistas E Formalistas Na Antropologia Econômica (Karl Polanyi and the 'Great Debate' Between the Substantivists and Formalists in Economic Anthropology) - Machado, Nuno Miguel Cardoso (Social Science Research Network, 2012)
Na raiz do pensamento Polanyiano, encontra-se a distinção entre economia no sentido substantivo e economia no sentido formal. Com efeito, a concepção substantivista que define a economia como um processo instituído de interação entre o homem e o ambiente natural e social que o rodeia e resulta em contínua oferta de meios para satisfazer as necessidades humanas constitui a base do método preconizado pelo autor: a análise institucional. Com tal distinção, Polanyi (1977a) pretende evitar a "falácia economicista" que consiste na identificação automática da economia com sua forma de mercado. Ao contrário, só na moderna economia capitalista é que um "sistema de mercados formadores de preços" desempenha papel fundamental. Essas questões foram alvo de um "Grande Debate" entre as correntes substantivista – encabeçada por Polanyi – e formalista no contexto da disciplina da Antropologia Econômica.At the root of Polanyian thought, a distintiction can be found between the substantive and formal concepts of the economy. In fact, the substantivist conception, that defines the economy as an instituted process of interaction between man and its natural and social environment, which results in a continuous supply of material means to meet human needs, constitutes the basis of the method recomended by the author: institutional analysis. With this distinction, Polanyi intends to avoid the "economistic fallacy", which consists of the automatic identification of the economy in its market form. Only in the modern capitalist economy does a system of "price-making markets" play a fundamental role. These questions were amply discussed in the so-called "Great Debate" between the substantivist and formalist schools of thought in the discipline of Economic Anthropology. in Economia e Sociedade, Vol. 21, No. 1 (44), pp. 165-195
Sociology; Anthropology
Keywords: economy; formalism; institutional analysis; market; substantivism